2021
DOI: 10.1002/jcp.30255
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin A gamma and NFATc3/SRPX2 axis contribute to human embryonic stem cell differentiation

Abstract: Our understanding of signaling pathways regulating the cell fate of human embryonic stem cells (hESCs) is limited. Calcineurin‐NFAT signaling is associated with a wide range of biological processes and diseases. However, its role in controlling hESC fate remains unclear. Here, we report that calcineurin A gamma and the NFATc3/SRPX2 axis control the expression of lineage and epithelial–mesenchymal transition (EMT) markers in hESCs. Knockdown of PPP3CC, the gene encoding calcineurin A gamma, or NFATC3, downregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…We found that SRPX2 was overexpressed in PTC and positively correlated with higher histological grade, metastatic lymph node grade, and worse prognosis. Previous studies have found that SRPX2 takes part in human embryonic stem cell differentiation, cognitive impairment, and epileptic activity [ 19 , 30 , 31 ]. Most published data show that SRPX2 has a carcinogenic effect and is abnormally expressed in various tumors [ 15 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that SRPX2 was overexpressed in PTC and positively correlated with higher histological grade, metastatic lymph node grade, and worse prognosis. Previous studies have found that SRPX2 takes part in human embryonic stem cell differentiation, cognitive impairment, and epileptic activity [ 19 , 30 , 31 ]. Most published data show that SRPX2 has a carcinogenic effect and is abnormally expressed in various tumors [ 15 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, inflammation can also promote the expression levels of SRPX2 [ 18 ]. Moreover, SRPX2 is regulated by its upstream molecules including TGFβR1/SMAD3, NFATc3/c-JUN, MAN1 (LEM) domain containing 1 (LEMD1), miR-149, and FOXP2 [ 17 , 19 22 ]. The effects of these mechanisms are not only limited to the upregulation of SRPX2 but also regulate the biological behaviors of tumor cell proliferation, migration, and invasion.…”
Section: Introductionmentioning
confidence: 99%
“…SRPX2 is a component in an extracellular matrix which involved in tumor formation including colorectal cancer [ 11 ], gastrointestinal cancer [ 12 ], and prostate cancer [ 13 ]. Additionally, SRPX2 exerts essential roles in pan-cancers because of participating in stem cell differentiation of human embryonic [ 14 , 15 ]. In PTC, SRPX2 has also been found significantly overexpressed and correlated with poorer disease-free survival of advanced PTC [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…SRPX2 is invasive by upregulating the FAK/SRC/ERK pathway and can lead to pancreatic cancer drug resistance in PI3K/AKT in lung cancer. Additionally, the NFATc3/SRPX2 axis participates in human embryonic stem cell differentiation, indicating that SRPX2 plays a critical role in pan-cancers (Gao et al, 2020;Li et al, 2020;Chen et al, 2021). SRPX2 is a component of the extracellular matrix, which is important for regulating tumor formation, as demonstrated in diverse tumors, such as colorectal cancer (Øster et al, 2013), gastrointestinal cancer (Tanaka et al, 2012), prostate cancer (Zhang et al, 2018), and pancreatic cancer (Gao et al, 2015).…”
Section: Discussionmentioning
confidence: 99%